The Effect of Nutrition Education with Audio Visual Media on Nutrition Knowledge and Attitudes on the Incident of Adolescent Gastritis at SMA Negeri 7 Samarinda - Zharfa Shabrina Dinnisa; Kurniati Dwi Utami; Mustaming; Joko Sapto Pramono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Gastritis is swelling due to inflammation in the mucosal lining of the stomach. Preliminary studies show that some adolescents with a history of gastritis have poor knowledge and attitudes. This study aims to determine the effect of nutritional education using audio-visual media on nutritional knowledge and attitudes and the incidence of juvenile gastritis. The research method is a quasi-experimental pretest-posttest nonequivalent control group design, which was carried out in March 2023. The research subjects were 50 students divided into two groups, namely the audiovisual group and the lecture group. Data analysis used the Paired Sample T-test and Mann-Whitney test. The research results found that audio-visual media had an effect on knowledge (p = 0.000) and attitudes (p = 0.000) compared to the lecture method. In conclusion, gastritis nutrition education using audio-visual media influences the knowledge and attitudes of teenagers at SMA Negeri 7 Samarinda.